Estimating DXA total body fat percentage by lipometer subcutaneous adipose tissue thicknesses - Tafeit, Erwin (Array, 2009)
Abstract: DXA is an accepted reference method to estimate body composition. However several difficulties in the applicability exist. The equipment is rather expensive, not portable, impractical for measurement of big study populations and it provides a minimal amount of ionizing radiation exposure. The optical device Lipometer (EU Pat.No. 0516251) provides non-invasive, quick, precise and safe measurements of subcutaneous adipose tissue (SAT) layer thicknesses at any site of the human body. Compared to DXA there are some advantages in the Lipometer approach, because this device is portable, quick, not expensive and no radiation is involved. To use these advantages in the field of total body fat% (TBF%) assessment, an acceptable estimation of DXA TBF% by Lipometer SAT thicknesses is necessary, which was the aim of this study. Height, weight, waist and hip circumferences, DXA TBF% and Lipometer SAT thicknesses at fifteen defined body sites were measured in 28 healthy men (age: 33.9 ± 16.6 years) and 52 healthy women (age: 40.1 ± 10.7 years). To estimate Lipometer TBF% stepwise multiple regression analysis was applied, using DXA TBF% as dependent variable. Using the fifteen Lipometer SAT thicknesses together with age, height, weight and BMI as independent variables provided the best estimations of Lipometer TBF% for both genders with strong correlations to DXA TBF% (R=0.985 for males and R=0.953 for females). The limits of agreement were –2.48% to +2.48% for males and –4.28% to +4.28% for females. For both genders we received a bias of 0.00%. The results of this paper extend the abilities of the Lipometer by a precise estimation of TBF% using DXA as "golden standard"